COMPARATIVE-TYPOLOGICAL CHARACTERISTICS OF ECONOMIC TERMS IN ENGLISH AND UZBEK LANGUAGES - Axmedov, Oybek; Djumambetova, Gulziba (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The article is devoted to the field of terminology in English and Uzbek languages, namely, creation of economic terms that actively used in economic activities. Moreover, this article provides a brief overview of the formation and construction of economic terms.